you multiply by using the formula
x1*x2=y1*y2
Answer:
x = 4 + √73
Step-by-step explanation:
The given equation is ( x-12 ) ( x + 4 ) = 9
We will solve the equation first.
( x - 12 ) ( x + 4 ) = 9
x( x+4 ) - 12 ( x + 4 ) = 9 [ Distributive property ]
x² + 4x - 12x - 48 = 9
x² - 8x - 48 = 9
x² - 8x - 48 - 9 = 0
x² - 8x - 57 = 0
[ x² - 2 (4x) + 16 ] - 57 - 16 = 0
(x - 4)² - 73 = 0
(x - 4)² = 73
( x-4 )² = √73
x = 4 + √73
x = 4 + √73 is the answer.
(Choice A)A
666
(Choice B)B
151515
(Choice C)C
202020
(Choice D)D
2323
or
False
Answer:
I think the answer is false I am not A 100%sure but most likely false
Step-by-step explanation: